Non-Desmoglein Antibodies in Patients With Pemphigus Vulgaris - Amber, Kyle T.; Valdebran, Manuel; Grando, Sergei A. (Frontiers in Immunology, 2018)
Pemphigus vulgaris is a potentially life-threatening mucocutaneous autoimmune blistering disease. Patients develop non-healing erosions and blisters due to cell-cell detachment of keratinocytes (acantholysis), with subsequent suprabasal intraepidermal splitting. Identified almost 30 years ago, desmoglein-3 (Dsg3), a Ca2+-dependent cell adhesion molecule belonging to the cadherin family, has been considered the ‘primary’ auto-antigen in pemphigus vulgaris. Proteomic studies have identified numerous autoantibodies in patients with pemphigus vulgaris that have known roles in the physiology and cell adhesion of keratinocytes. Antibodies to these autoantibodies include desmocollins 1 and 3, several muscarinic and nicotinic acetylcholine receptor subtypes, mitochondrial proteins, HLA molecules, thyroid peroxidase, and hSPCA1, the Ca2+/Mn2+-ATPase encoded by ATP2C1 which is mutated in Hailey-Hailey disease. Several studies have identified direct pathogenic roles of these proteins, or synergistic roles when combined with Dsg3. We review the role of these direct and indirect mechanisms of non-desmoglein autoantibodies in the pathogenesis of pemphigus vulgaris.